2019
DOI: 10.3390/s19030687
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Monocular Visual Odometry for Turbid and Dynamic Underwater Environments

Abstract: In the context of underwater robotics, the visual degradation induced by the medium properties make difficult the exclusive use of cameras for localization purpose. Hence, many underwater localization methods are based on expensive navigation sensors associated with acoustic positioning. On the other hand, pure visual localization methods have shown great potential in underwater localization but the challenging conditions, such as the presence of turbidity and dynamism, remain complex to tackle. In this paper,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 65 publications
0
24
0
Order By: Relevance
“…The feature points satisfying the motion estimation of the camera are static features and the others are considered as dynamic features. Maxime et al [19] propose real-time monocular visual odometry for dynamic underwater environments. They utilize RANSAC to compute the essential matrix and eliminate the outliers that are not consistent with the epipolar geometry.…”
Section: Dynamic Slammentioning
confidence: 99%
“…The feature points satisfying the motion estimation of the camera are static features and the others are considered as dynamic features. Maxime et al [19] propose real-time monocular visual odometry for dynamic underwater environments. They utilize RANSAC to compute the essential matrix and eliminate the outliers that are not consistent with the epipolar geometry.…”
Section: Dynamic Slammentioning
confidence: 99%
“…Under the water, because of the complexity of the environment and thus difficulty to obtain very accurate 3D measurements, comparative studies have been focused on simulated trajectories (Duarte et al, 2016) or on comparing real-time results with photogrammetrically derived trajectories obtained offline, in post processing, using for example BINGO software or Agisoft Photoscan (Drap et al, 2015;Nawaf et al, 2018) or Colmap structure from motion application (Ferrera et al, 2019). A real accuracy assessment of visual odometry and SLAM techniques, evaluated against a ground truth surveyed using an independent and more accurate method is still missing.…”
Section: Motivations and Aimmentioning
confidence: 99%
“…Under the water, SLAM techniques have been used to fuse inertial and acoustic positioning systems in particular in subsea metrology industry (IMCA, 2017), or for autonomous underwater robot navigation and localization using imaging sonar and visual sensors. First methods were focused on using acoustic images (Fusiello et al, 1999;Castellani et al, 2005;Roman 2005, Clark et al, 2008Ribas et al, 2009) to move then to visual based methods (Eustice et al, 2008;Kim and Eustice 2009;Duarte et al, 2016, Ferrera et al, 2019. A more comprehensive review of different techniques used for localization and mapping can be found in Paull et al (2014) and Hidalgo and Bräunl (2015).…”
Section: Slam Structure From Motion and Visual Odometrymentioning
confidence: 99%
See 1 more Smart Citation
“…They provide a wide range of utilities, from marine investigation [1,2], to archaeology [3] or structures monitoring [4,5]. Particularly interesting is the use of computer vision for underwater robot localization [6], for which expensive sensors based on acoustic technologies have been mainly used to date [7].…”
Section: Introductionmentioning
confidence: 99%